Language Models are the new Doom - Madeira, Caio; Magnaguagno, Maurício Cecílio; Griebler, Dalvan (Anais da Escola Regional de Aprendizado de Máquina e Inteligência Artificial da Região Sul (ERAMIA-RS), 2025)
As more devices include a display, more probable they may run Doom. Various techniques are used to limit the processing required by the game. A parallel can be drawn with small language models, which are being ported to a wide variety of devices, including legacy ones. While less capable than their large-scale counterparts, these models retain the essence of natural language processing. In this work, we map parallels between Doom and language models, focusing on a TinyLlama model trained on the TinyStories dataset ported to the PlayStation Portable, with hyper-parameter value experimentation.